Lactate as a Predictor of Occult Hypoperfusion in Major Trauma Patient (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Occult hypoperfusion is an inadequate tissue perfusion in spite of having normal traditional vital signs. Most of the major trauma patient suffers from tissue hypoxia which usually remain undetected and its consequences increases both morbidity and mortality. Early detection and correction of occult hypoperfusion decrease morbidity and mortality in trauma victims.The aim of the study is to detection of occult hypoperfusion in major trauma patient by measuring serum lactate level.Materials and methods: This was a prospective observational study performed in the Casualty Unit and Orthopedic Department of Chittagong Medical College Hospital from November 2018 to October 2019. Sample size was 70. Enrolment of patients was done by purposive random sampling fulfilling the selection criteria. Serum lactate was measured within 48 hours of admission. Systolic blood pressure, heart rate, injury severity score, and the urine output were measured at patient’s admission. All variables were recorded and analyzed. Statistical significance was defined as p< 0.05 and Confidence Interval (CI) set at 95% level.Results: Seventy patients were enrolled in the study, mean age of 32.93 ± 12.06 years. Most of the patients were male. Occult hypoperfusion found in fifty four (77%) patients with serum lactate (Mean±SD) 4.81±3.19mmol/L. Sixteen (23%) patients were not hypoperfused with serum lactate 1.41 ± 0.39mmol/L. Length of hospital stay was 14.07 ±10.07 days. Occult Hypoperfusion in respect to mortality and survival where sensitivity was 100%, specificity was 26.2. Sepsis with occult hypoperfusion. SSI(68.66%), WD(12.9%), Sepsi (40%), RTI(50%), ARDS(10%), MODS(7.1%), ICU care in (8.6%) patients. Nine (12.9%) patients died sixty one (87.1%) survived.Conclusion: Serum lactate can detect occult hypoperfusion and appeared as a reliable marker predicting the outcome in trauma victims.JCMCTA 2023 ; 34 (1) : 69-73